Aspekty prawne wejścia do sąsiedniego budynku, lokalu lub na teren sąsiedniej nieruchomości w prawie budowlanym - Sługocka, Martyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
According to Article 47 paragraph 1 of the Act — Construction Law if an investor has to do the work in the neighboring property, they must obtain the consent of the owner of this property. If the owner does not agree, the investor can benefit from the help of administration which will allow decisions to enter someone else’s property. The question of compensation must be established between the investor and the owner. The authorities have no power to negotiate between the parties.
Keywords: entering property; neighboring property; preparatory work; investor; building permit